The technical school and professional training from a gender perspective in the province of Corrientes (Argentina) - D'Andrea, Ana María (2019)
Historically, technical-professional education is characterized by presenting the characteristics of sexual discrimination and the sexual part of culturally crystallized work. However, women have been introduced gradually in this type of educational offer. The objective of this article is to present the perspective of gender in technical secondary schools and vocational training centers in terms of the reasons that influenced the choice of the same, the evaluation of the received training and future expectations. It is a qualitative study of descriptive scope. Focus groups were used, with men and women separately, from an intentional sample of three technical schools that have offers of secondary education and professional training from the province of Corrientes (Argentina). About the reasons that affect the choice of modality, no differences are found in men and women. Regarding the evaluation of the training received, the study of secondary education refers to educational differences differentiated according to gender, which is considered discriminatory by women. About future expectations, everyone agrees on women. It is concluded that the main difference between male cursors and women in secondary education and vocational training is the majority of the rights acquired in recent times by younger women. Thus, the influences of feminist movements in Argentina go through the pores of institutions as traditional as educational ones